MANAGEMENTS MORNING GLORY IN COMPETITION WITH MAIZE IN ORGANIC SYSTEM - Giraldeli, Ana Ligia; Fontanetti, AnastÃ¡cia; Monquero, PatrÃcia Andrea (REVISTA DE AGRICULTURA, 2019)
One of the biggest obstacles to organic maize cultivation is weed management. The aim of this work was to evaluate the mowing and weeding in the control of densities of Ipomoea triloba (morning glory) in competition with maize. The experiment was installed in a completely randomized design, with four replications, in the factorial scheme 3 x 3 + 1. The first factor was constituted by three densities of the species I. triloba and the second by three weed management. The additional treatment consisted in the cultivation of maize free from I. triloba interference. The mowing done in the V4 stage of maize did not minimize the competition of I. triloba. Weeding was more efficient for control at higher densities. The I. tribola showed regrowth and despite accumulating reduced dry mass, it was more efficient in the uptake of N, P, K, and Mg in relation to the uncropped plants.